How catching the interstellar wind in the inner solar system led the way on a road to interdisciplinary research between heliophysics and astrophysics - Möbius, Eberhard (Frontiers in Astronomy and Space Sciences, 2023)
Combined in situ observations of the interstellar wind through the solar system and of its pickup ions (PUIs), implanted after ionization in the solar wind, explain, in comparison with interstellar absorption lines of nearby stars, that the Sun is in an interaction region of the two nearest interstellar clouds. This new finding disrupts the long-held understanding that we are inside the local interstellar cloud (LIC). We discuss how space physics evolved toward such interdisciplinary studies between heliophysics and astrophysics. In 1984, the discovery of interstellar He+ PUIs exposed the very local interstellar medium to in situ diagnostics at 1AU. These PUIs provide the interstellar gas composition and form a stepping stone for the acceleration of ions, especially into anomalous cosmic rays. Using the Sun as a gravitational spectrograph, direct imaging of the neutral interstellar wind, first for He and then for H, O, and Ne, provides the interstellar gas velocity vector and temperature at the heliopause. Combining the interstellar gas flow vectors, those of secondary neutral He and O, and the interstellar magnetic field direction deduced from the interstellar H deflection and termination shock anisotropy seen by the Voyagers provides synergistically the heliosphere’s shape, its interaction with the interstellar medium, and constrains our radiation environment. This ISMF organizes the bright Ribbon seen in all-sky images of energetic neutral atoms with the potential to provide its precision determination. The elemental and isotopic composition from PUI and neutral gas observations constrains the galactic evolution and Big Bang cosmology, opening additional interdisciplinary opportunities.